2022
DOI: 10.1186/s42408-022-00132-9
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation’s influence on fire behavior goes beyond just being fuel

Abstract: Background The structure and function of fire-prone ecosystems are influenced by many interacting processes that develop over varying time scales. Fire creates both instantaneous and long-term changes in vegetation (defined as live, dead, and decomposing plant material) through combustion, heat transfer to living tissues, and subsequent patterns of recovery. While fuel available for combustion may be relative to the amount of vegetation, it is equally instructive to evaluate how the physical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…These data are particularly useful in ecosystems dominated by fine scale variation in surface fuels (Hiers et al 2009) and for inputs into high resolution coupled fire-atmosphere models (Linn et al 2001, Mell et al 2009, Linn et al 2020) that operate in three dimensions with the ability to represent withinstand variability (Hiers et al 2020). Such high-resolution representation of fuel variation will improve our prediction of heterogeneity in fire effects and the underlying physical influences of vegetation on the fire environment [13]. In this study, we found that the variability in surface mass across these two burn units (658 ha total) was considerable (mean: 841 g m -2 , stdev: 350 g m -2 from the 'Total 0-30' model (Figure 2), highlighting the need to think beyond stand level averages [66].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data are particularly useful in ecosystems dominated by fine scale variation in surface fuels (Hiers et al 2009) and for inputs into high resolution coupled fire-atmosphere models (Linn et al 2001, Mell et al 2009, Linn et al 2020) that operate in three dimensions with the ability to represent withinstand variability (Hiers et al 2020). Such high-resolution representation of fuel variation will improve our prediction of heterogeneity in fire effects and the underlying physical influences of vegetation on the fire environment [13]. In this study, we found that the variability in surface mass across these two burn units (658 ha total) was considerable (mean: 841 g m -2 , stdev: 350 g m -2 from the 'Total 0-30' model (Figure 2), highlighting the need to think beyond stand level averages [66].…”
Section: Discussionmentioning
confidence: 99%
“…In southeastern U.S. ecosystems where production and turnover rates are high [19,20], repeated burning provides a continuum of fine surface fuels and live vegetation that enable a broad range of fire behavior throughout the year [21,22]. As such, the low (often <1m height) vegetation (shrubs, grasses, forbs, leaf litter, soil organic layer, and small coarse wood) continuously changes with each fire and ecological response [13], making estimates of surface vegetation structure and loading, notwithstanding fuel moisture dynamics [23], highly variable at fine temporal (<hr) and spatial scales (<1m). Furthermore, large diameter coarse woody debris (>20 cm) have little opportunity to accumulate and hence contribute little to combustion during prescribed burns because of their high moisture retention and fast decay rates [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though these approaches have been successfully used by managers in a variety of situations, including large-scale fire management, they do not provide information on the fine-scale variability in fuels that drive fire behavior and effects in prescribed fires and in frequently burned ecosystems. There are no operational products that provide information on the finer scale attributes of surface vegetation composition and architecture, despite research in laboratory, field, and modeling environments that have identified these biophysical characteristics as drivers of variation in fire behavior and in the effects of surface fires [13][14][15][16][17]. Thus, improving estimation of the spatial resolution of fuels, and including information about the vertical dimensionality of the fuelbed architecture or the 3D characteristics of surface living and dead vegetation, are critical to improving the prediction of low-intensity surface fire behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In southeastern U.S. ecosystems, where production and turnover rates are high [19,20], repeated burning provides a continuum of fine surface fuels and living vegetation that enable a broad range of fire behavior throughout the year [21,22]. As such, the low (often <1 m height) vegetation (shrubs, grasses, forbs, leaf litter, soil organic layer, and small coarse wood) continuously changes with each fire and ecological response [13], making estimates of surface vegetation structure and loading, notwithstanding fuel moisture dynamics [23], highly variable at fine temporal (<hr) and spatial scales (<1 m). Furthermore, large diameter coarse woody debris (>20 cm) have little opportunity to accumulate, and hence contribute little to combustion during prescribed burns because of their high moisture retention and fast decay rates [24,25].…”
Section: Introductionmentioning
confidence: 99%